Managing Advanced HIV Disease in a Public Health Approach. (4th March 2018) - Ford, Nathan; Meintjes, Graeme; Calmy, Alexandra; Bygrave, Helen; Migone, Chantal; Vitoria, Marco; Penazzato, Martina; Vojnov, Lara; Doherty, Meg; ,
Abstract: In 2017, the World Health Organization (WHO) published guidelines for the management of advanced human immunodeficiency virus (HIV) disease within a public health approach. Recent data suggest that more than a third of people starting antiretroviral therapy (ART) do so with advanced HIV disease, and an increasing number of patients re-present to care at an advanced stage of HIV disease following a period of disengagement from care. These guidelines recommend a standardized package of care for adults, adolescents, and children, based on the leading causes of morbidity and mortality: tuberculosis, severe bacterial infections, cryptococcal meningitis, toxoplasmosis, and Pneumocystis jirovecii pneumonia. A package of targeted interventions to reduce mortality and morbidity was recommended, based on results of 2 recent randomized trials that both showed a mortality reduction associated with delivery of a simplified intervention package. Taking these results and existing recommendations into consideration, WHO recommends that a package of care be offered to those presenting with advanced HIV disease; depending on age and CD4 cell count, the package may include opportunistic infection screening and prophylaxis, including fluconazole preemptive therapy for those who are cryptococcal antigen positive and without evidence of meningitis. Rapid ART initiation and intensified adherence interventions should also be proposed to everyone presenting with advanced HIV disease.